Penguatan Sosiologi Keluarga Di Dunia Digital: Studi Literasi Pengasuhan Anak Usia Dini Berbasis Keluarga - Darni, Melia; Perdana, Dedy Ilham (Prodi Sosiologi Universitas Mataram, 2024)
The role in child development in the digital era, the digital era is very influential on a child's development in terms of positive and negative impacts and where there is a very high increase in technological developments that affect the style and lifestyle of children in the digital era.Of course the role of parents in this case is very important due to the impact of the acceleration of technology which is very increasing so that access is very easy, so the role of a parent in this case to supervise a child in using technology in the digital era is never separated from related objects related to access to an internet. The research method in this study is to use literacy studies related to parenting in the advanced era and take case examples from various sources in Indonesia in the last 10 years with an approach from Leedy which focuses on synthesizing between data to obtain relean results and criticize the data which aims as a search for new sources of knowledge on certain social problems, especially on the role of parents and children. The result is that there are three main indicators in positioning parents in dealing with Generation Z, namely as content filters, as technology mentors, and as positive models in early childhood. In addition, authoritative parenting is found to provide limits to children about good and bad things, encourage children's creativity so that children can be adaptive to technology, introduce digital literacy, and collaborative processes with third parties in the form of schools, tutoring, children's social spaces, and informal institutions.